Dynamic response of an infinite beam supported by a saturated poroelastic halfspace and subjected to a concentrated load moving at a constant velocity. (15th June 2016) - Shi, Li; Selvadurai, A.P.S.
Highlights: Contact problem of an infinite beam and a poroelastic halfspace is investigated. Bounding techniques are used to prescribe the boundary conditions on the interface. Equivalent stiffness of the halfspace is derived using contour integration method. Two critical velocities are identified for the moving constant load. Solutions for poroelasticity can be analytically reduced to those for elasticity. Abstract: The steady-state displacements and moments in a Bernoulli–Euler beam of finite width and infinite extent, resting on a poroelastic halfspace and subjected to a concentrated load moving at a constant velocity, were investigated using the concept of the equivalent stiffness of the halfspace. Expressions for the equivalent stiffness of the saturated poroelastic halfspace interacting with the infinite beam of finite width were derived analytically using a contour integration procedure. The influence of adhesion and drainage effects between the beam and the halfspace surface is accounted for by considering "bounding techniques" for prescribing the boundary conditions at the interface. Comparisons have been made between situations for the elastic and poroelastic halfspace with regard to their equivalent stiffness and the dynamic responses of the beam for different velocities of the moving load.